THE MORPHOSYNTAX OF CAUSATIVE CONSTRUCTION IN DAWAN LANGUAGE - Benu, Naniana N.; Daar, Gabriel Fredi (Journal of Language, Education, Literature, and Culture, 2023)
In order to understand the structure, procedure, and causative marking of the Dawan language, this paper addresses causative construction in the Dawan language. Since the writer is a native speaker of the language, the primary data from the field study was corroborated by written materials like the bible in the Dawan language as well as by intuitive data. The elicitation technique combined the two sets of data to obtain valid data. The outcome demonstrates four distinct forms of causative construction: affixation, complex sentences, verb serialisation, and the addition of a causer argument. The transitive form, derived from an intransitive clause, adds the causer argument. S is transferred to the O function, and a causer argument is added to the A function. The conjunction natuin or fun indicates causative marking in a complex sentence. This study considers the Dawan language's causative verb serialisation the most fruitful construction. There are two types of this construction: causative serialisation and cause-effect serialisation. In the first type, V1 is an action verb with the lexical meaning "causative," V2 is the outcome (effect) of what V1 has done. In contrast to the first, the causative verbs moe/mo'e "make" and eik "bring" occupy V1 in causative serialisation, while the outcome of the action in V1 occupies V2. The final method is causative construction by affixation, or the morphological process.